ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œAll-on-FourÃƒÂ¢Ã¢â€šÂ¬Ã‚Â Immediate Function Concept and Clinical Report of Treatment of an Edentulous Mandible with a Fixed Complete Denture and Milled Titanium Framework - Amir H. Khatami, DDS1 & Christopher R. Smith, DDS, FACP2 (Journal of Prosthodontics, 2008)
The ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œAll-on-FourÃƒÂ¢Ã¢â€šÂ¬Ã‚Â conceptÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Âtilting the distal implants in the edentulous arches improves the prosthetic supportÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Âincreases the inter-implant distance and provides better implant anchorage in the bone by using longer implants